Tapak Tilas Agama Khonghucu Di Indonesia Dan Korelasi Ajaran Wu-Chang Dalam Menjaga Integrasi Nasional - Kasyfurrahman, Taufiq Nur; Azhari, Alwi Ghiyaz; Hekmatiyar, Eros Samudera (AL-ADYAN, 2020)
Indonesia is a country that consists of various kinds of SARA (Tribe, Agma, Race, and Intergroup). Confucius is one of the officially recognized religions in Indonesia. Confession Confucius as the official religion in Indonesia has a somewhat complicated footprint, because there are pros and cons to its existence in Indonesia. Apart from that, Confucianism has the teachings of Wu-Chang which contains about the five moral attitudes that must be held by its adherents. This teaching certainly contributes to maintaining the Integration of the Republic of Indonesia. This study aims to analyze the existence of Confucianism in Indonesia and the implementation of the teachings of Wu-Chang in maintaining national integration. The method used is descriptive qualitative method by collecting data from observations, interviews, documentation, and literature studies. The results of this study show a historical description of the existence of Confucianism in Indonesia and the correlation of the teachings of Wu-Chang in maintaining national integration.